Benefit Incidence of Public Transfers: Evidence from the People's Republic of China - Shen Ke; Sang-Hyop Lee (Asian Development Bank (ADB), 2014)
Benefit incidence analyses provide important insights into problems facing any government struggling to deliver essential and equitable social services. Utilizing the framework of the National Transfer Accounts Project, this paper analyzes the benefit incidence of public transfers across generations and socioeconomic groups in the People's Republic of China in 2009. Public education transfers were equally distributed by residence, gender, and income groups at the primary and secondary levels but favored city dwellers, females, and the wealthy at the tertiary level. Public health-care programs tended to equally target the young and middle-aged from different socioeconomic groups but tilted toward urban dwellers, males, and higher income groups at older ages. Public pension spending strongly favored high-income groups, with rural residents, females, and lower income groups receiving greatly reduced benefits. Our results also indicate that total public spending favored elderly people as spending per person 65 years and older was twice that per child younger than 19. In the next 10 or 20 years, the government should endeavor to improve and strengthen public support systems. In addition to this effort, the currently fragmented health insurance system and pension system should move toward a unified system to reduce inequalities in benefit incidence across socioeconomic groups.
hdl:11540/1278
Keywords: E62; H53; O15; 330; benefit incidence; public transfers; the People's Republic of China